Factors of International Business Environment, Research of them and the Role in the Development of European Business - Perminienė, Neringa; Vengrauskas, Petras Vytautas (Ekonomika, 2001)
Novelty of the theme. Theme of international business is rather new. There are a few researches on practical and theoretical aspects on international business both on global and European sphere. However, they arc rather fragmentary, concerning on one or another business field. A lack of these data forces us to establish the main research methodics that aid us to understand problems of today’s businessman trying to enter to foreign market. Scientific problem is described by two sentences: 1) adopting of general business theory for estimating of environment factors, for development of international business on the European market scale, 2) possibilities of adopting of European countries experience to foreseeing trends of Lithuanian business environment development. Here you find a short situation of business, choosing out the main peculiarities of local, national, European, multinational and global companies, in this article. After the analysis of main differences between these companies, we have presented methodics of business environment researches and influence of these factors on European business development. In order to explain more clearly influence of these factors on strategic decisions of businessmen, there are presented some practical examples how international business representatives should act in one or another dynamic European business environment There are presented concrete business environment factors in European market: taxes politics, politic, human resources and etc., in the third part. Finally, there are underlined business environment factors that have influence on European market business men strategy. On the base of this article, we can underline the main business environment problems that arise in European market everyday. It is more easy to foreseen for businessman how to enter with his own goods or services, that barriers could appear in establishing a retailing in Italy, Russia or Lithuania. Conclusions of the article: 1) establishment of single market forces European businessman to search for possibilities to develop business abroad, that directly depends on business environment; 2) European market creates the possibility to enter for new business unit, that are represented by European, multinational and global companies; 3) there is a necessity for using LEPESTC model for businessman environment research to include one more factory - cultural environment C (LEPESTC-C); 4) the main factors, that should be estimated arc: government politic, taxes for firms; law; region politics, local infrastructure, human resources, national culture; 5) for development of business in European market are necessary to estimate: law in EU, environment factors politics in EU, regional politics, distribution possibilities, migration of labour, capital migration, social politics, competition, politic in actual business field.